De hand van Huizinga - Huizinga, Johan (Amsterdam University Press, 2009)
This book contains a unique new selection of his most important essays from the extensive oeuvre of the Dutch historian Johan Huizinga. These essays and studies have been chosen on the basis of the different subject matter that Huizinga was involved in; ranging from the Middle Ages, Renaissance, Modern History and Cultural History in general. These selections are introduced and illuminated by Prof. dr. Willem Otterspeer who is also Huizinga's biographer. Johan Huizinga was born in Groningen, in 1872. He studied Dutch and Oriental language and literature at the University of Groningen (1891 - 1895) and comparative linguistic at the University of Leipzig (1895-1896). In 1915, he was appointed professor of general history at the Leiden University. His most famous works include The Autumn of the Middle Ages (1919), which dealt with life, ideas, art, and behaviors of the upper classes of Burgundy in the 14th and 15th centuries, Erasmus (1924), a biography of the famous Dutch Renaissance scholar, and Homo Ludens (1938), focusing on the element of play in human culture.